Research on performance optimization of Loess-based ceramic membrane supports with Bauxite-dolomite-talc as additives. (1st March 2022) - Tong, Zhi; Liu, Lu; Yang, Xiaoyu; Li, Dachuan; Guo, Lei; Zhang, Jianxu
Abstract: Inorganic ceramic membranes have attracted much attention due to their advantages of long life, acid and alkali corrosion resistance, and easy cleaning, but they have not been widely used due to the high cost. In order to obtain a ceramic membrane with low cost and good performance, in this paper, loess-based ceramic membrane support was prepared by using loess as raw material, bauxite as aluminum source, dolomite as pore-forming agent and talc as plasticizer. Response surface optimization was used to determine the optimal addition parameters of ingredients. In addition, the factors affecting the performance of the supports were analyzed in terms of material composition, microscopic morphology, and porosity. The results show that the addition of talc conduced to avoid the negative impact of the pore-forming effect of dolomite on the mechanical strength of the support, and the optimum proportioning parameters are 48.85 wt% of bauxite, 9.93 wt% of dolomite and 8 wt% of talc. Under this condition, the bending strength was 42.24 MPa, the pure water flux was 8323.73 l·m −2 ·h −1 ·MPa −1, and the average pore throat radius was 5.15 μ m. The performance of the best sample reaches the application performance of porous ceramic supports, which provides a theoretical basis for the wide application of low-cost ceramic membrane supports.